Analisis Kualitas Pelayanan dan Brand Image Terhadap Loyalitas Pelanggan Dengan Kepuasan Sebagai Variabel Intervening di CV. Prakarsa Indo Karya - Juliansyah, Ari; Reynilda, Reynilda; Hadzami, Meizha (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
Although Pangkalpinang City has an administrative government, one of the companies engaged in the printing sector, in this case CV. Prakarsa Indo Karya has experienced a decline in turnover since the last three years. In fact, the market share of the company that was established in 2019 is dominated by elements within the Pangkalpinang City Government. Sales activities carried out can be in the form of procuring printing needs, office stationery, to food and beverage needs within the Pangkalpinang City Government. Analyzing the relationship between service quality and customer loyalty, Brand Image and customer loyalty, service quality and satisfaction, Brand Image and satisfaction, service quality and customer loyalty with satisfaction as an intervening variable, and Brand Image and customer loyalty with satisfaction as an intervening variable at CV is the challenge of this study, according to Prakarsa Indo Karya. This study employs quantitative research with 61 respondents, and the data analysis method makes use of both direct and indirect validity, reliability, and hypothesis testing. Every instrument from every variable was deemed valid and reliable based on the results of the validity and reliability tests. There is no direct relationship between the service quality variable and customer loyalty, no direct relationship between the Brand Image variable and customer loyalty, a direct and significant relationship between the service quality variable and satisfaction, no direct relationship between the satisfaction variable and customer loyalty, no relationship between the service quality variable and customer loyalty with satisfaction acting as an intervening variable, and no relationship between the Brand Image variable and customer loyalty with satisfaction acting as an intervening variable, according to the results of the hypothesis testing that was conducted at CV. Prakarsa Indo Karya.